INDONESIAN MIGRATION INDUSTRY IN TAIWAN: SOME SOCIO-ECONOMIC IMPLICATIONS AND IMPROVEMENT CHALLENGES - Paulus Rudolf Yuniarto (Jurnal Kajian Wilayah, 2015)
Institutional placement mechanisms are inevitable in migrant services industries. However, some business components in the recruitment process are unbalanced, whereby the migrant workers are entirely responsible for their departure costs and fees. Individual and institutional actorsbanks, insurance companies, brokers, and private or even state recruitment institutionsare involved in the migrant workers sales market, and these conditions are faced by Indonesian migrant workers in general. As a result, debt bondage and slavery are typically characteristic of Indonesian migrant workers. Using existing literature and a qualitative approach through case studies of Indonesian migrant workers in Taiwan, this article demonstrates the role of brokers (agencies) in managing and controlling migrant labor abroad. Even some of the placement and fiancial policies designed to help migrants with their debt bondage and agency exploitation are also prone to manipulation. Therefore, this article also explores what circumstances and conditions might lead Indonesian migrant workers in Taiwan to debt bondage and suggests improvements for migrant empowerment. Keywords: debt, slavery, migration industry, brokers (agency)